Antenna rotation error tolerance for a low-frequency aperture array polarimeter - Sutinjo, Adrian; Hall, Peter (IEEE, 2014)
We present antenna rotation error tolerance analysis for a polarimeter consisting of dual-linearly polarized dipole-like elements. Treating the elements as a phased array and expressing the measurement basis as circularly polarized (CP) results in a concise expression for the Jones matrix for the array. For the type of elements being considered, the matrix shows that the intrinsic cross-polarization ratio (IXR) of the array at the intended beam scanning direction is unaffected by small rotation errors. For random rotation error and very large number of elements, we further find that the relative Jones matrix estimation error converges to that of the error-free case at the intended beam scanning direction; however, the effect of element rotation error on array directivity and radiation pattern remains. Recasting the analysis with the array observing an unpolarized source, a relation between rotation error and cross-polarization “leakage” is obtained, wherein similar trends with very large number of elements hold true. Practical examples involving “large” number of elements such as the low frequency Square Kilometre Array are discussed.